Use of the elevated T-maze to study anxiety in mice - Carvalho-Netto, E. F.; Nunes-De-Souza, R. L. (Elsevier B.V., 2004)
We have recently suggested that the elevated T-maze (ETM) is not a useful test to study different types of anxiety in mice if a procedure similar to that originally validated for rats is employed. The present study investigated whether procedural (five exposures in the enclosed arm instead of three as originally described for rats) and structural (transparent walls instead of opaque walls) changes to the ETM leads to consistent inhibitory avoidance acquisition (IAA) and low escape latencies in mice. Results showed that five exposures to the ETM provoked consistent IAA, an effect that was independent of the ETM used. However, the ETM with transparent walls (ETMt) seemed to be more suitable for the study of conditioned anxiety (i.e. IAA) and unconditioned fear (escape) in mice, since IAA (low baseline latency with a gradual increase over subsequent exposures) and escape (low latency) profiles rendered it sensitive to the effects of anxiolytic and anxiogenic drugs. In addition to evaluation of drug effects on IAA and escape, the number of line crossings in the apparatus were used to control for locomotor changes. Results showed that whereas diazepam (1.0-2.0 mg/kg) and flumazenil (10-30 mg/kg) impaired IAA, FG 7142 (10-30 mg/kg) did not provoke any behavioral change. Significantly, none of these benzodiazepine (BDZ) receptor ligands modified escape latencies. The 5-HT1A partial receptor agonist buspirone (1.0-2.0 mg/kg) and the 5-HT releaser fenfluramine (0.15-0.30 mg/kg) impaired IAA and facilitated escape, while the full 5-HT1A receptor agonist, 8-OH-DPAT (0.05-0.1 mg/kg) and the 5-HT2B/2C receptor antagonist, SER 082 (0.5-2.0 mg/kg) failed to modify either response. mCPP (0.5-2.0 mg/kg), a 5-HT2B/2C receptor agonist, facilitated IAA but did not alter escape latency. Neither antidepressant utilized in the current study, imipramine (1.0-5.0 mg/kg) and moclobemide (3.0-10 mg/kg) affected IAA or escape performance in mice. The well-known anxiogenic drugs yohimbine (2.0-8.0 mg/kg) and caffeine (10-30 mg/kg) did not selectively affect IAA, although caffeine did impair escape latencies. Present results suggest the ETMt is useful for the study of conditioned anxiety in mice. However, upon proximal threats (e.g. open arm exposure), mice do not exhibit escape behavior as an immediate defensive strategy, suggesting that latency to leave open arm is not a useful parameter to evaluate unconditioned fear in this species. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: inhibitory avoidance acquisition; one-way escape; elevated T-maze; anxiolytic and anxiogenic drugs; mice